1992
DOI: 10.1021/bp00014a012
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for Disruption of Microbial Cells with Pressurized Carbon Dioxide

Abstract: Disruption of microbial cells by pressurized carbon dioxide at both subcritical and supercritical temperatures has been previously investigated. This method differs in principle from other disruption techniques and was found to have potential applications for rupture of a variety of microorganisms. However, it is not as effective for some of the microbial cells, including yeast, of which the cell walls are extremely robust and rigid. This work suggests an alternative operation to improve the disruption rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 4 publications
5
39
1
1
Order By: Relevance
“…Although Lin et at. have observed an improvement in the disruption and inactivation rates of baker's yeast with a series of pressure release/recompression treatments with CO 2 gas in the range between 1000psi (about 68.0atm) and 3000psi (204 atm) , 5,6) these results suggest that the explosive decompression of CO 2 would influence the survival ratio of the yeast cells to a lesser extent, at least with our system. Our previous observations with a scanning electron microscope have shown that the yeast cells, at the least some of them, may be mechanically ruptured by the CO 2 treatment with explosive decompression.…”
supporting
confidence: 49%
“…Although Lin et at. have observed an improvement in the disruption and inactivation rates of baker's yeast with a series of pressure release/recompression treatments with CO 2 gas in the range between 1000psi (about 68.0atm) and 3000psi (204 atm) , 5,6) these results suggest that the explosive decompression of CO 2 would influence the survival ratio of the yeast cells to a lesser extent, at least with our system. Our previous observations with a scanning electron microscope have shown that the yeast cells, at the least some of them, may be mechanically ruptured by the CO 2 treatment with explosive decompression.…”
supporting
confidence: 49%
“…In view of the static pressure obtained herein, it was expected that CO 2 diffusion into the cell would alter its chemical composition and wall structure enough to result in cell rupture after immediate pressure release at the die exit. Other authors have observed cell rupture after a sudden release of CO 2 atmosphere at static pressures of similar order of magnitude of those reached in this work (SHIMODA et al, 2001;DEBS-LOUKA et al, 1999;YANG;CHEN, 1992;LIN et al, 1991). However, these researchers kept cells under pressure for several minutes, whereas the present process was much shorter.…”
Section: Estimation Of Residence Time Distributionsupporting
confidence: 78%
“…It is suggested that the CO 2 inhibitory effect may be linked to changes in permeability and structure of cell membrane and to changes of enzymatic synthesis at the cytoplasm (DIXON; KELL, 1989). Some authors also demonstrated that pressurized CO 2 causes cell disruption when pressure as low as 5 MPa is suddenly released (SHIMODA et al, 2001;DEBS-LOUKA et al, 1999;YANG;CHEN, 1992). During food extrusion processes, similar level of pressure on the food mass is observed, followed by a sudden pressure drop at the die exit.…”
Section: Introductionmentioning
confidence: 99%
“…There are several old and new applications for the supercritical fluid (SCF) technology in bioprocessing, including the nonthermal cell inactivation (Dillow et al, 1999;Spilimbergo and Bertucco, 2003;Hong and Pyun, 2001), permeabilization (Aaltonen and Rantakyla, 1991), extraction of fermentation products (Bruno et al, 1993;Hampson and Ashby, 1999;Isenschmid et al, 1995), removal of biostatic agents and organic solvents from fermentation broth, SCF disruption of yeasts (Castor and Hong et al, 1995;Lin and Chen, 1994;Lin et al, 1992;Nakamura et al, 1994) and bacteria (Juhasz et al, 2003;Khosravi-Darani et al, 2004), destruction of industrial waste (Kim and Hong, 2001), fractionatation and purification of biopolymers (Khosravi-Darani et al, 2003), removal of chlorinated compounds from water, and treatment of lignocellulosic materials (Puri, 1983). Some products possibly produced by the SCF technology may be found in processes to obtain vitamin additives, de-alcoholized beverages, de-fat potato chips, and encapsulated liquids.…”
Section: Introductionmentioning
confidence: 99%
“…This chapter has focused on SCF special applications in the field of food biotechnology. The application of SCF is simple, inexpensive, and noninjurious to the structure and function of enzymes (Lin et al, 1992) and protein activities (Kamat et al, 1995;Zheng and Tsao, 1996;Kasche et al, 1988). The supercritical carbon dioxide (SC-CO 2 ) is the most commonly used Low-value, High-volume (LVHV) products (Vijayan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%